Strafrecht und Demokratie Zürich 2022 - Staffler, Lukas; Ege, Gian; Jany, Oliver; Lichtenberger, Luisa; Payer, Andrés; Ranzoni, Luca; Reinicke, Franziska; Schweiger, Theresa; Tsilikis, Dimitrios (Nomos Verlagsgesellschaft mbH & Co. KG, 2023)
Criminal law and democracy are closely intertwined. A closer view of this connection, however, reveals manifold challenges that arise from pandemics or fake news, but also from the actors influencing the legislative process. In addition, fundamental legal-theoretical and legal-practical questions emerge in dealing with the principle of legality in criminal matters. The 9th Young Criminal Law Symposium examined selected research questions that arise from this for the criminal law sciences. Topics of the contributions include the internationalisation of criminal law, the actors shaping criminal law as well as constitutional-theoretical and legal-philosophical emphases of the principle of legality. With contributions by Francesca Bonzanigo, MLaw; Dr. Luka Breneselović, LL.M.; Giulia Canova, B.A.; Jun.-Prof. Dr. Ivó Coca-Vila; Tommaso Giardini, M.A.; Jessica Krüger, MPhil (Cantab); Lisa Kujus; Prof. Dr. Maria Ludwiczak Glassey; Prof. Dr. Matthias Mahlmann; Mag. Lukas Emanuel Müller, BA, LL.M. (Leiden); StA Simon Pschorr; Hugo Soares, LL.M. (Lisbon) and Dr. Alexandra Windsberger.